Uma análise sobre as soft skills relevantes para profissionais de requisitos em projetos de software - Valle, Romulo Antonio Garcia da Rosa do (2025)
The Requirements Engineering (RE) is crucial for the success of software projects, as it establishes the foundation for developing systems that are efficient and aligned with the needs of end users and stakeholders. In this context, soft skills play a fundamental role in RE, being as highly valued as technical skills due to their impact on project success. The objective of this research is to develop an analysis based on the mapping and categorization of soft skills commonly cited in both academia and industry, in relation to the RE process in software development. The methodology was structured into five main stages: (1) conducting systematic searches in the IEEE and Scopus databases to identify soft skills frequently reported in the RE literature; (2) analyzing the Chaos Report 2022: Beyond Infinity to identify core principles of project success and map soft skills linked to these principles; (3) grouping and categorizing the soft skills identified from both academic and industry sources; (4) conducting interviews with software engineers and requirements analysts working in the Brazilian market to validate the selected soft skills and their categorization; and (5) critically analyzing the relationship between the identified soft skills and the principles from the Chaos Report, in order to assess the impact of these skills on RE practices. The contributions include: (i) identifying soft skills related to RE practices; (ii) categorizing these soft skills based on the three Chaos Report factors (Sponsor, Team, and Place); and (iii) developing an analysis to help RE professionals identify behavioral competencies for career improvement.